GE_GERICHTE C/25066/2011 vom 29. Juni 2012 - GE Cour de justice (2012)
MOTIVATION; LÉGITIMATION ACTIVE ET PASSIVE; MASSE EN FAILLITE | LP.204; LP.207; CPC.311.1; CPC.138.3.A; CPC.143.1; CPC.257.1; CPC.254